UJI EFEKTIVITAS EKSTRAK ETANOL KULIT BUAH LABU SIAM (Sechium edule (Jacq.) Swartz ) SEBAGAI DIURETIK PADA TIKUS JANTAN GALUR WISTAR (Rattus novergicus) - Lumban Gaol, Riris Iriany (UNIVERSITAS SAM RATULANGI, 2014)
The study aimed at finding out the effectiveness of chayote (Sechium edule (Jacq.) Swartz) rind ethanol extract as diuretic and the relationship of the increases dose of chayote rind ethanol extract. Completely randomized design method was used in this experiment. The subject of the experiment were fifteen white male rats strain Wistar (Rattus novergicus) were divided into five groups of treatment, namely negative control group (CMC 0,5% suspension), positive control group (furosemide suspension), the dose 0,033 g/kg bw of chayote rind ethanol extract group, the dose 0,066 g/kg bw of chayote rind ethanol extract group, and the dose 0,132 g/kg bw of chayote rind ethanol extract group. The test of diuretic effect were conducted by calculate volume of excreted urine during 6 hours treatment. The results show, diuretic activity increases on the giving of chayote rind ethanol extract. Data were analyzed using spss ver.16. the differences between treatments were analyzed using one way ANOVA. The dose of chayote rind ethanol extract 0,033 g/kg bw was the most optimum diuretic activity. The increasing dose of chayote rind ethanol extract did not show a better result. Key words : Sechium edule (Jacq.) Swartz, diuretic effectiveness, Rattus novergicus